Highly unsaturated fatty acid synthesis in vertebrates: new insights with the cloning and characterization of a delta6 desaturase of Atlantic salmon - Zheng, Xiaozhong; Tocher, Douglas R; Dickson, Cathryn; Bell, J Gordon; Teale, Alan J (Lipids, 2005)
Fish are an important source of the n-3 highly unsaturated fatty acids (HUFA), eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids that are crucial to the health of higher vertebrates. The synthesis of HUFA involves enzyme-mediated desaturation, and a ∆5 fatty acyl desaturase cDNA has been cloned from Atlantic salmon (Salmo salar) and functionally characterized previously. Here we report cloning and functional characterisation of a ∆6 fatty acyl desaturase of Atlantic salmon, and describe its genomic structure, tissue expression and nutritional regulation. A salmon genomic library was screened with a salmon ∆5 desaturase cDNA and positive recombinant phage isolated and subcloned. The full-length cDNA for the putative fatty acyl desaturase was shown to comprise 2106bp containing an ORF of 1365 bp specifying a protein of 454 amino acids (GenBank accession no. AY458652). The protein sequence included three histidine boxes, two transmembrane regions, and an N-terminal cytochrome b5 domain containing the haem-binding motif HPGG, all of which are characteristic of microsomal fatty acid desaturases. Functional expression showed that this gene possessed predominantly ∆6 desaturase activity. Screening and sequence analysis of the genomic DNA of a single fish revealed that the ∆6 desaturase gene comprised 13 exons in 7965 bp of genomic DNA. Quantitative real time PCR assay of gene expression in Atlantic salmon showed that both ∆6 and ∆5 fatty acyl desaturase genes, and a fatty acyl elongase gene, were highly expressed in intestine, liver and brain, and less so in kidney, heart, gill, adipose tissue, muscle and spleen. Furthermore, expression of both ∆6 and ∆5 fatty acyl desaturase genes in intestine, liver, red muscle and adipose tissue was higher in salmon fed a diet containing vegetable oil than in fish fed a diet containing fish oil.